Parental leave and the social politics of fatherhood in Spain - Flaquer, Lluís; Escobedo, Anna (Cuadernos de Relaciones Laborales, 2014)
In this article we analyse in the first place the different employment impact of fatherhood and motherhood. The analysis of longitudinal data from the Spanish Social Security shows how the birth of the first child is a turning point from which there appears to be a divergence between male and female employment trajectories so that for fathers this juncture is clearly associated with an intensification of their breadwinning role. This finding prompts us to explore the development of the social politics of fatherhood in Spain to the extent to which father involvement in the care of children constitutes a key factor to enhance equal opportunities between men and women as well as to improve child well-being levels. To this end, we focus on the emergence of parental leaves for men to turn then to study the evolving regulation of parental leave in Spain from a comparative perspective. In the final part of the article we analyse data and we propose indicators of paternity leave take-up, following the upgrading of this benefit in 2007, shortly before the start of the financial crisis. In spite of cutbacks resulting from the recession, our data indicate that paternity leave take-up rates in relation to potential male users have increased from 2008 to 2011, although significant variations appear by region, educational attainment and quality of employment.
Keywords: emerging new parenting styles; parental leave; paternity leave; social politics of fatherhood